Protective Roles of Sodium Butyrate in Lipopolysaccharide-Induced Bovine Ruminal Epithelial Cells by Activating G Protein-Coupled Receptors 41 - Yang, Tianyu; Datsomor, Osmond; Jiang, Maocheng; Ma, Xiaoyu; Zhao, Guoqi; Zhan, Kang (Frontiers in Nutrition, 2022)
This study aimed to evaluate whether sodium butyrate (SB) attenuates the ruminal response to LPS-stimulated inflammation in bovine rumen epithelial cells (BRECs). BRECs were exposed to 0.5 mM SB for 18 h as a pretreatment. BRECs pretreated with SB were used for the SB group, and those subjected to a 4 μg/mL lipopolysaccharide (LPS) challenge for 6 h were used for the LPS pretreated with SB (LSB) group. GPR41KD BRECs pretreated with SB were used for the SB group and then induced by LPS (GPR41KD-BRECs). The LPS-induced BRECs showed increases in the expression of genes related to pro-inflammation and decreases in the expression of genes related to tight junction proteins; these were attenuated by pretreatment with SB. Compared with that in LPS-stimulated BRECs, the ratio of phosphorylated NF-κB (p65 subunit) to NF-κB (p65 subunit) and the ratio of phosphorylated IκBα to IκBα were suppressed with SB pretreatment. The LSB group abated LPS-induced apoptosis and decreased the expression of Bax, Caspase 3, and Caspase 9 mRNA relative to the LPS group. In addition, the LSB group had a lower proportion of cells in the G0-G1 phase and a higher proportion of cells in the S phase than the LPS group. Genes (ACAT1 and BDH1) related to Volatile Fatty Acid (VFA) metabolism were upregulated in the LSB group compared to those in the LPS-induced BRECs. In addition, pretreatment with SB promoted the gene expression of GPR41 in the LPS-induced BRECs. Interestingly, GPR41KD BRECs abrogated these effects. Our results suggest that SB pretreatment protects against the changes in BRECs that occur during the LPS-induced inflammatory response, which is concurrent with an enhanced ketogenic metabolism and upregulated epithelial barrier function by activating GPR41.